(untitled) (Journal of Nepal Geological Society, 2000)
In a study of landslide risk assessment, one of the main problems is to define a univocal methodology for evaluating this risk and mapping it. Starting from the available data about this topic and, in particular, from the report of Varnes and IAEG ( 1984) edited by UNESCO and synthesised in Italy by Canuti and Casagli (1994), Crescenti (1998) published a critical review of the definitions related to landslide risk evaluation. In fact, treating " hazard " and " the probability of landslide occurrence" as synonymous, does not seem correct, since the term "hazard" corresponds to the real danger situation in a site for the advancing phenomenon . Instead, the probability does not show the real danger state, because not all the landslide phenomena are dangerous for the elements at risk. Furthermore, among the field experts (consultants and decision-makers) the term "hazard" is instinctively connected with the real danger, which is related not only to the probability of occurrence of a landslide phenomenon, but also to its intensity. It is therefore more reasonable to define landslide hazard on the basis of both aspects. With this hazard definition, the way to evaluate the landslide risk has to be reconsidered as well as a new definition of vulnerability is required. In this paper, we applied this methodology for the study of landslides at the Guardiagrele Village, a historical site of Central Italy. The village may be considered to be a representative of other similar villages situated in this part of the Apennines.